Tanggap Pertumbuhan dan Produksi Sawi (Brassica juncea L.) pada Pemberian Pupuk Cair - Muhammad Rizky Andry; Ratna Rosanty lahay; Revandi I M Damanik (Universitas Sumatera Utara, 2015)
The objective of this research was acquired of effect on addition of liquid fertilizer of growth and production of mustard greens. Therefor, research has been conducted at experimental field of Agriculture USU (± 25 m asl.) in August-September 2014 using a randomized block design with one factor. that was addition of liquid fertilizer consist of control, basic fertilizer (urea, SP36, KCl), organic liquid fertilizer (1, 2 and 3 ml/l water per plant) and anorganic liquid fertilizer (1, 5, 3, and 4,5 ml/l water per plant). The results showed that 2 and 3 weeks after planting (MST) of plant height, 2, 3, and 5 MST of leaf total, fresh root weight, sell fresh weight be significantly different of addition liquid fertilizer. We recommend that basic fertilizer should be given on mustard greens cultivation, because the results on growth and production of mustard greens was well.Keywords : Mustard Greens, Fertilizer, Liquid Fertilizer